1993
DOI: 10.1002/mar.4220100407
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of the kapferer‐laurent consumer involvement profile scale

Abstract: The Consumer Involvement Profile (CIP) is tested across several samples of U.S. consumers. With one exception, the authors were able to successfully replicate the factor structure of the CIP, thereby concluding that the scale is a useful measure of several antecedents of involvement. However, two factors purporting to measure interest versus pleasure regularly merged into a single factor. The authors conclude that interest and pleasure cannot be distinguished from one another in the current applications. © 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 8 publications
5
25
0
2
Order By: Relevance
“…Factor 1 suggests that consumer interest in clothing stems from the fact that it (1) gives them pleasure and enjoyment and (2) helps shape their image (is a means of self-expression). The pleasure and enjoyment aspects of interest highlight the experiential aspect of clothing and confirm that hedonism is closely related to the involvement concept (Kapferer and Laurent, 1985b;Rodgers and Schneider, 1993). Although interest and pleasure have been hypothesised as separate dimensions of involvement, their merging together is consistent with other research.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Factor 1 suggests that consumer interest in clothing stems from the fact that it (1) gives them pleasure and enjoyment and (2) helps shape their image (is a means of self-expression). The pleasure and enjoyment aspects of interest highlight the experiential aspect of clothing and confirm that hedonism is closely related to the involvement concept (Kapferer and Laurent, 1985b;Rodgers and Schneider, 1993). Although interest and pleasure have been hypothesised as separate dimensions of involvement, their merging together is consistent with other research.…”
Section: Discussionsupporting
confidence: 66%
“…Thirty-two items were derived from the literature (Lastovicka and Gardner, 1979;Laurent, 1985a, 1985b;Bloch et al, 1986;Higie and Feick, 1989;Jain and Srinivasan, 1990;Rodgers and Schneider, 1993;Van Trijp et al, 1996). These items correspond to the five dimensions of involvement reported above (importance [10 items], interest [6 items], sign value/symbolic [6 items], self-expression [2 items] and hedonic/pleasure aspect [8 items]).…”
Section: An Examination Of Involvement With Clothesmentioning
confidence: 99%
“…For the product ballpoint pen, the symbolic value and pleasure resulted in a single dimension. In the research by Rodgers and Schneider (1993), where the CIP scale was tested in four product categories (electronic equipment, audio recorders, cars and clothing), the union of the importance and pleasure dimensions was observe in all those products. Jain and Srinivasan (1990) conducted an empirical test of comparison between the scales proposed by Ratchford (1987), Higie and Feick (1989), McQuarrie and Munson (1987), Zaichkowsky (1985) and .…”
Section: Consumer Involvement Profile (Cip) Scalementioning
confidence: 96%
“…In the study by Quester and Lim (2003), the interest (product importance) and pleasure dimensions resulted in a single dimension for the sneakers product, and the symbolic value and pleasure dimensions also resulted in a single dimension for the ballpoint pen product. Rodgers and Schneider (1993) observed the union of the interest (product importance) and pleasure dimensions in electronic equipment, audio recorders, cars and clothing. In the Brazilian context, Fonseca and Rossi (1999) observed the union of the product importance and pleasure dimensions for the product beer.…”
Section: B) Reliability and Validity Of The Nip Scale In The Studied mentioning
confidence: 99%
“…Further research has either entirely or partially adopted these constructs in tourism and leisure studies (Gross & Brown, 2006Gursoy & Gavcar, 2003;Kyle, Graefe, Manning, & Bacon, 2004;Kyle & Mowen, 2005;Wiley, Shaw, & Havitz, 2000). Another study that tested the performance of CIP on US consumers confirmed that the constructs are reliable (Rodgers & Schneider, 1993).…”
Section: Involvementmentioning
confidence: 89%